Optimalisasi Kunjungan Posyandu Balita Melalui Program Inovasi Pokban Dan Posyandu Ceria di Rw 8 Kelurahan Karangroto, Kecamatan Genuk, Kota Semarang - Hanifatur Rosyidah; Fifiana Lisani; Ikha Himatul Ulya; Ikliyla Fitri; Khuzaimah Adinda; Risa Febriyani; Zulfa Nursyinta A (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Posyandu is a social institution that functions as basic social services and other services according to the potential of each region. Advocacy activities for the head of the posyandu aim to bring the posyandu closer to residents, increase visits by mothers who bring toddlers to the posyandu with a target of 90% success, but coverage has not yet reached the target. Posyandu for toddlers in RW 8 KelurahanKarangroto has been formed, but based on the survey results it was found that the cause of the problem regarding monitoring the growth and development of toddlers is the lack of attitudes and behavior of the mother which is supported by the long distance of the posyandu. The aim of this activity is to increase the coverage of posyandu in RW 8, Karangroto Village, Genuk District, Semarang City. The activity was carried out in RW 8 Karangroto Village, Semarang City with the target of mothers with children under five years of age. The form of activity is "Ceria Posyandu" by providing education to parents of toddlers, realizing posyandu with 5 tables, and a playground for toddlers to increase toddlers' interest. The activity was carried out well and smoothly, where a sample of 58 toddlers was obtained from RW 8 Karangroto Village. There was an increase in the pre-post test, the results of the Wilcoxon test obtained p = 0.01 (p <0.05) so it can be concluded that there was a statistically significant difference in knowledge before and after being given the intervention. After this activity ends, it is hoped that the Posyandu Ceria will remain active and run regularly.